Impact of Job Satisfaction and Personal Values on the Work Orientation of Chinese Accounting Practitioners - Lan, George; Okechuku, Chike; Zhang, He; Cao, Jianan (2013)
This study investigates the impact of job satisfaction and personal values on the work orientation of accounting practitioners in China. Satisfaction with work varies across individuals and how individuals view work (i.e., work orientation) may depend not only on satisfaction with various facets of their work but also on their beliefs and values. We used the questionnaire from Wrzesniewski et al. (J Res Pers 31, 21–33, 1997) to measure work orientation. Job satisfaction was measured by the Job Descriptive Index (JDI) developed by Smith et al. (The Measurement of Satisfaction in Work and Retirement. Rand McNally, Skokie, IL, 1969) and personal values were measured by the Schwartz Value Questionnaire Survey (Schwartz, Adv Exp Social Psychol 25, 1–65, 1992). Our sample consisted of 370 accounting practitioners from six major cities in China; 268 were females and 102 were males. We found that 41.9 % of the respondents viewed their work as a career, 37.6 % as a calling and 20.5 % as a job and that job satisfaction to be the highest among the “calling” group and lowest among the “job” group. There were no significant gender differences in the work orientation of the respondents. Our study showed that the value types achievement and hedonism and satisfaction with promotion were significant predictors of the career orientation, while the value type benevolence and satisfaction with the present job were predictors of the calling orientation. Dissatisfaction with work was the major predictor of the job orientation. Furthermore, length of employment was positively associated with both the calling and job orientation, but negatively associated with the career orientation.
Keywords: Chinese accountants; personal values; Job satisfaction; Calling; Career; Job; Work orientation